Numerical Simulation of a Small-Scale Cyclone Separator using MP-PIC Method. (November 2019) - Wargadalam, V J; Andira, M A; Putra, C A; Siswantara, A I; Gunadi, G G R; Hariyotejo,; Damis, C; Aminuddin,
Abstract: This paper presents a numerical study of a small-scale cyclone separator performance by means of computational fluid dynamics (CFD). The family of Euler-Lagrange approach named multiphase particle-in-cell (MP-PIC) is employed for modelling gas-solid interaction. The three-dimensional small-scale cyclone separator geometry was discretized with hexahedral-dominant mesh. The gas phase is assumed to be a flue gas which density is 0.363 kg/m 3 and dynamic viscosity is 7.47E-5 Pa s. The solid particles are catalyst used in a small-scale fluid catalytic cracking (FCC) unit which are having 2400 kg/m 3 of density and diameters vary from 90 µm to 130 µm. Large Eddy Simulation (LES) turbulence model was used to accurately predict turbulent flow behaviour of flue gas inside the cyclone. The simulation was performed for 7.82 m/s inlet velocity for both flue gas and catalyst. The pressure drop and catalyst collection efficiency were the variables of interest to be analysed, which were compared to the analytical solutions. It was found that the results generated from numerical simulation using MP-PIC method reflect a good agreement with the analytical solutions.